RANCANG BANGUN SISTEM KEAMANAN DATABASE DENGAN METODE KRIPTOGRAFI (Studi Kasus PT. SUMBER SOLUSI KOMUNIKASI BANDUNG) - Ardi Taryanto (INFOKOM (Informatika & Komputer), 2018)
This research was aimed to find out and analyze information systems procurement of goods at PT. Sources Communication Solutions as a solution to data security problems. Security systems use classical cryptographic methods by means of chipher substitution, is that each character in the plaintext will be replaced with another letter based on a particular method or formula so that it cannot be understood by other parties The research method used is a qualitative descriptive method. While the data collection techniques are carried out by means of observation and literature study. The concept of system design refers to data processing of procurement of goods both from inputting to reporting. So that this application design is expected to become an information system with better data security and a solution for the company.